A Review of the Principal’s Management in Enhancing Professional Learning Community Activities at SMPN 9 Tenggarong - Apriliyani Apriliyani; Akhmad Akhmad; Sudarman Sudarman; Moh Bahzar; Widyatmike Gede Mulawarman; Usfandi Haryaka (FKIP - Universitas Riau, 2026)
This study examined the management of the Professional Learning Community (Komunitas Belajar Profesional/KBP) “Komunitas Etam Belajar” at SMPN 9 Tenggarong in supporting the implementation of the Merdeka Curriculum. A qualitative case study approach was employed involving eight informants, including the principal, vice principal, teachers, administrative staff, and parents. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings indicate that KBP is effectively managed through needs-based planning, clear task distribution, collaborative digital discussions, and participatory monitoring based on the Educational Report Card. Despite limited facilities and infrastructure, the school optimized digital resources and implemented peer tutoring to support teacher learning. Adaptive leadership by the principal played a key role in sustaining KBP activities and fostering collaboration among teachers. These findings suggest that effective KBP management contributes to improving teacher competence and strengthening school quality in implementing the Merdeka Curriculum.